2002
DOI: 10.1097/00004770-200208000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of Various Root Canal Preparation Techniques: An In Vitro Comparative Study

Abstract: In this study, we compared the antimicrobial efficacy of various root canal preparation techniques and instruments in the root canals of 40 human first maxillary premolars extracted for orthodontic reasons. After extirpation of the pulp, teeth were sterilized in an autoclave. Then, the root canals were infected with Enterococcus faecalis suspension and the teeth incubated at 37 degrees C for 24 h. Thereafter, the teeth were divided into five groups: preparation with K-file or K-Nitiflex file (step-back techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 7 publications
0
32
0
4
Order By: Relevance
“…2 Various studies have demonstrated that mechanical preparation with hand instruments and irrigation with saline cannot predictably eliminate the bacteria from the infected root canals. [3][4][5] Therefore, the current focus of interest has been the use of irrigating solutions with strong antibacterial activity as the necessary supplement to mechanical preparation. Even after meticulous mechanical procedures along with the use of irrigating solutions, some bacteria can still be recovered from the canals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Various studies have demonstrated that mechanical preparation with hand instruments and irrigation with saline cannot predictably eliminate the bacteria from the infected root canals. [3][4][5] Therefore, the current focus of interest has been the use of irrigating solutions with strong antibacterial activity as the necessary supplement to mechanical preparation. Even after meticulous mechanical procedures along with the use of irrigating solutions, some bacteria can still be recovered from the canals.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the samples with positive culture before root canal obturation had only 68% of complete periapical healing (3) . In infected and necrotic root canal systems, bacteria grow mostly in sessile biofilms, aggregates, and coaggregates in which they are embedded in an extracellular matrix material (4) . Factors that contribute to a persistent periradicular infection after root canal treatment include Most persistent organism that, despite making up a small proportion of the flora in untreated canals, plays a major role in the aetiology of persistent periradicular lesions after root canal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Sodium hypochlorite (NaOCl) is the most commonly used endodontic irrigant because of its antimicrobial potential 4 and its ability to dissolve organic matter. 5 However, it is not only irritant to the vital periradicular tissues, but also inherently possesses certain disadvantages such as inability to remove the smear layer, unpleasant taste, high toxicity, 6 corrosive to instruments, reduction in elastic modulus, and flexural strength of dentin.…”
Section: Introductionmentioning
confidence: 99%
“…Frente à metodologia empregada neste trabalho, destaca-se por ser amplamente utilizada para a avaliação da descontaminação do canal radicular (Menezes et al, 2004;Vivacqua-Gomes et al, 2005;Gurgel-Filho et al, 2007;Manzur et al, 2007;Metzger et al,2007;Martinho;Gomes 2008;Camara et al, 2009;Ozdemir et al, 2010;Dornelles-Morgental et al, 2011;Lima et al, 2012), bem como para a análise do preparo mecânico (Siqueira Jr et al, 1997;Dalton et al, 1998;Siqueira Jr et al, 1999;Card et al, 2002;Coldero et al, 2002;Pataky et al, 2002;Rollison et al, 2002;Siqueira Jr et al, 2002;McGurkin-Smith et al, 2005;Berber et al, 2006;Chuste-Guillot et al,2006;Aydin et al, 2007;Hockett et al, 2008;Machado et al, 2010;Singla et al, 2010;Siqueira Jr et al, 2010;Paranjpe et al, 2012).…”
Section: Resultsunclassified
“…Os motivos pelo uso do hipoclorito de sódio, como irrigante, deu-se ao O primeiro está relacionado a uma redução significativa da infecção após o preparo biomecânico: os valores são reforçados por diferentes estudos encontrados na literatura (Dalton et al, 1998;Siqueira Jr et al, 1999;Coldero et al, 2002;Siqueira Jr. et al, 2002;Pataky et al, 2002;McGurkin-Smith et al, 2005;Berber et al, 2006;Chuste-Guillot et al,2006;Aydin et al, 2007;Machado et al, 2010;Siqueira Jr. et al, 2010;Paranjpe et al, 2012). Na avaliação comparativa entre os grupos, as mesmas tendências foram observadas.…”
Section: Resultsunclassified